2019
DOI: 10.1145/3326337
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence, Artists, and Art

Abstract: This study examines how people perceive artwork created by artificial intelligence (AI) and how presumed knowledge of an artist's identity (Human vs. AI) affects individuals’ evaluation of art. Drawing on Schema theory and theory of Computers Are Social Actors (CASA), this study used a survey-experiment that controlled for the identity of the artist (AI vs. Human) and presented participants with two types of artworks (AI-created vs. Human-created). After seeing images of six artworks created by either AI or hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Under the new creation concept, the traditional means and the current means will be very different, the creation method is more and more rich and diverse, the creation content is newer, the art of combining digital and multimedia also pays more attention to the development of personality, and the needs of different audience groups are satisfied. e difficulty of creation lies in new ideas, once any creation lacks new ideas, it is difficult to get people's love, and the art of combining digital and multimedia is no exception [17][18][19]. With the emergence of the art of combining digital and multimedia, some old artists do not have a deep enough understanding of this new form of creation and cannot break through themselves in time with the development of the times.…”
Section: Digital Media Artmentioning
confidence: 99%
“…Under the new creation concept, the traditional means and the current means will be very different, the creation method is more and more rich and diverse, the creation content is newer, the art of combining digital and multimedia also pays more attention to the development of personality, and the needs of different audience groups are satisfied. e difficulty of creation lies in new ideas, once any creation lacks new ideas, it is difficult to get people's love, and the art of combining digital and multimedia is no exception [17][18][19]. With the emergence of the art of combining digital and multimedia, some old artists do not have a deep enough understanding of this new form of creation and cannot break through themselves in time with the development of the times.…”
Section: Digital Media Artmentioning
confidence: 99%
“…In a similar vein, Lima et al (2020) found online users to only marginally denounce the idea of an AI system holding the copyright of its own generated art. Other studies found AI-generated art being evaluated unfavorably vis-a-vis their human-created counterparts (Hong and Curran, 2019;Ragot et al, 2020), even though people do not seem to be able to differentiate between them (Köbis and Mossink, 2021;Gangadharbatla, 2021).…”
Section: Artificial Intelligence-generative Modelsmentioning
confidence: 99%
“…When we create we reflect, sometimes those reflections make it into our research. Some of our work is creation for creation's sake, or a way of thinking [17]: artworks do not have to have a purpose. That said, perhaps we might also find meaning in formalising and exposing these hidden artistic practices that are typically considered "hobbies" or "soft skills" to give them credence and credit where it is due.…”
Section: Reflection and Open Questionsmentioning
confidence: 99%
“…There is both tension and understanding between person and machine, the barriers between what constitutes `art' are becoming blurred. On one hand, where how can traditional creative practices find a home in our digital age [15,35], and on the other, how can those works created with and by technology find acceptance amongst ones created by more traditional means [9,17]? There are also divides between our artistic endeavours and our research, for some these are clear cut, for others it is almost impossible to draw the line between the two.…”
Section: Tension/easementioning
confidence: 99%